Sosialisasi Pengembangan Ekowisata Dalam Meningkatkan Ekonomi Masyarakat Di Desa Wiring Tasi Kecamatan Suppa Kabupaten Pinrang - Ansir Launtu; Ardiansyah Halim; Syamsul Alam; Yana Fajriah; Hasbiyadi Hasbiyadi; M.Irwan N.H; Jumiati Jumiati (Jurnal Kabar Masyarakat, 2024)
This service activity aims to socialize the development of ecotourism in improving the community’s economy. This activity was carried out in collaboration with STIEM Bongaya Makassar with partner institutions in this activity, namely TJSL, PT PLN (Persero), Lowita Coastal Youth Community. The number of coastal communities involved in the Talkshow activities was 15 residents. The activity will take place on November 4 and 5 2023. The activity method is carried out by means of Simulation, Discussion and Question and Answer. The results of this socialization activity are expected to become a reference for the government in formulating policies in the tourism sector. The establishment of facilities to support community participation in tourism development and development is something that the government should not miss because whatever form of development it takes, it must always prioritize the impact it will have on the community, including tourism development. In this way, it is hoped that the government’s support will be prioritized in efforts to improve the economy and community welfare. Assistance - assistance from the government can be provided to support community participation in tourism development and development, both in capital, assistance, training and marketing.